The Influence of Patient Safety Culture, Nurse Handover Communication, and Patient Safety Knowledge on the Implementation of Safety Goals in the Inpatients at Dr. H. Seowondo Kendal Regional Hospital - Aldika (Syntax Literate, 2025)
Patient safety is a crucial indicator in healthcare services, as stipulated in Minister of Health Regulation No. 11 of 2017 through the implementation of the Six Patient Safety Targets (SKP). Implementation of the SKP still faces challenges, such as poorly documented Nurse Handover Communication (KHP), insufficient attention to medication safety, and suboptimal infection control. to analyze the influence of patient safety culture, nurse handover communication, and patient safety knowledge on the implementation of SKP in the inpatient ward of Dr. H. Soewondo Kendal Regional Hospital. This quantitative cross-sectional study used primary data. The sample consisted of 144 inpatient nurses selected through a total sampling technique. The instrument was a questionnaire with Likert and Guttman scales that had been tested for validity and reliability. Data were analyzed using SPSS version 26.0. Simple linear regression and Spearman correlation showed that all three independent variables had a significant partial effect on the implementation of SKP. Patient safety culture had the strongest effect, followed by nurse handover communication and patient safety knowledge. Meanwhile, the F-test analysis showed that patient safety culture, nurse handover communication, and patient safety knowledge had a significant simultaneous effect on the implementation of SKP. There is a significant influence of patient safety culture, nurse handover communication and patient safety knowledge on the implementation of patient safety targets, both partially and simultaneously.